A nomogram with the peripheral blood neutrophil-to-lymphocyte ratio before treatment predicts the survival of patients with nasopharyngeal carcinoma - Zhang, Huai-wen; Feng, Liu; Pang, Hao-wen; Yu, Teng-hua; Lu, Tian-zhu; Li, Jin-gao; Xu, Bin; Jiang, Chun-ling (Frontiers in Oncology, 2025)
BackgroundThis study was performed to investigate the relationship of the pretreatment neutrophil count and neutrophil-to-lymphocyte ratio (NLR) with the prognosis of nasopharyngeal carcinoma (NPC), as well as to establish an NLR-related nomogram to predict survival in patients with NPC.MethodsIn total, 747 patients with NPC were enrolled between January 2005 and January 2015 at our hospital. Kaplan–Meier survival analysis was used to evaluate overall survival (OS), progression-free survival (PFS), and distant metastasis-free survival (DMFS), with comparisons made using the log-rank test. Univariate and multivariate Cox regression analyses were conducted to identify independent risk factors for OS, PFS, and DMFS. The optimal NLR cut-off value was determined using receiver operating characteristic curve analysis. A nomogram model was then constructed and validated using R software (Version 3.6.0).ResultsAmong the 747 patients, N stage (P = 0.01, 0.042, 0.017) and NLR (P = 0.037) were identified as independent predictors of DMFS. Independent predictors of OS were sex (P = 0.024), age (P = 0.019), N stage (P = 0.006, 0.031, 0.002), American Joint Committee on Cancer (AJCC) stage (P = 0.003), adjuvant chemotherapy (P = 0.016), and NLR (P = 0.036). N stage (P = 0.001, 0.0221, 0.003), AJCC stage (P = 0.001), and NLR (P = 0.035) were also associated with PFS. The prognostic model showed good agreement with actual outcomes. Compared with the TNM staging system, the nomogram demonstrated superior accuracy and stability.ConclusionsIn patients with NPC, an elevated pretreatment NLR was associated with poorer OS, PFS, and DMFS. The NLR-based nomogram provided more accurate survival prediction than clinical staging and may serve as a valuable tool in guiding prognosis and treatment planning.